PENERAPAN MODEL BRAIN BASED LEARNING BERNUANSA LINGKUNGAN SEKITAR DALAM MENINGKATKAN PEMAHAMAN SISWA PADA PEMBELAJARAN IPA DI KELAS V SEKOLAH DASAR - Dudu Suhandi Saputra; Yuyu Yulianti; Wulandari Juwita Agustina (Jurnal Lensa Pendas, 2019)
This research is motivated by the low ability of students to understand science, research aims to improve students' comprehension skills in Grade V science learning in Cikasarung I Elementary School through the application of the environment-based brain-based learning model. This research is a classroom action research where the researcher cooperates with the fifth grade teacher of SD Negeri Cikasarung I as an observer. The research subjects were 24th grade students of SD Negeri Cikasarung I consisting of 12 male students and 12 female students. The techniques used in data collection are tests, observations, interviews and documentation. Data obtained in the form of test results as primary data and the results of observations, interviews and documentation as secondary data. The data analysis technique used is qualitative descriptive analysis for observations of each cycle. The results showed that the application of the brain based learning model with the nuances of the environment in science learning can improve the understanding of fifth grade students of Cikasarung Elementary School I. Conclusion, the application of the environment-based brain based learning model can improve students' understanding of fifth grade science learning at SD Negeri Cikasarung I.